External and circadian inputs modulate synaptic protein expression in the visual system of Drosophila melanogaster - Krzeptowski, Wojciech; Gorska-Andrzejak, Jolanta; Kijak, Ewelina; Gorlich, Alicja; Guzik, Elzbieta; Moore, Gareth; Pyza, Elzbieta M. (Frontiers in Physiology, 2014)
In the visual system of Drosophila melanogaster the retina photoreceptors form tetrad synapses with the first order interneurons, amacrine cells and glial cells in the first optic neuropil (lamina), in order to transmit photic and visual information to the brain. Using the specific antibodies against synaptic proteins; Bruchpilot (BRP), Synapsin (SYN) and Disc Large (DLG), the synapses in the distal lamina were specifically labeled. Then their abundance was measured as immunofluorescence intensity in flies held in light/dark (LD 12:12), constant darkness (DD), and after locomotor and light stimulation. Moreover, the levels of proteins (SYN and DLG), and mRNAs of the brp, syn and dlg genes, were measured in the fly’s head and brain, respectively. In the head we did not detect SYN and DLG oscillations. We found, however, that in the lamina, DLG oscillates in LD 12:12 and DD but SYN cycles only in DD. The abundance of all synaptic proteins was also changed in the lamina after locomotor and light stimulation. One hour locomotor stimulations at different time points in LD 12:12 affected the pattern of the daily rhythm of synaptic proteins. In turn, light stimulations in DD increased the level of all proteins studied. In the case of SYN, however, this effect was observed only after a short light pulse (15 min). In contrast to proteins studied in the lamina, the mRNA of brp, syn and dlg genes in the brain was not cycling in LD 12:12 and DD, except the mRNA of dlg in LD 12:12. Our earlier results and obtained in the present study showed that the abundance of BRP, SYN and DLG in the distal lamina, at the tetrad synapses, is regulated by light and a circadian clock while locomotor stimulation affects their daily pattern of expression. The observed changes in the level of synaptic markers reflect the circadian plasticity of tetrad synapses regulated by the circadian clock and external inputs, both specific and unspecific for the visual system.